The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.35940/ijeat.f1063.0986s319
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Growth Temperature on TiO2 Nanostructures by Hydrothermal Synthesis

Abstract: Titanium dioxide (TiO2) shows a great interest in solar cell application due to its morphology and crystalline structure. Moreover, it is an affordable compound that could make solar cells more economical than traditional silicon solar cells. In this study, one-step hydrothermal method is demonstrated to synthesis TiO2 nanorods/nanoflowers morphology on different hydrothermal reaction temperature. Increasing the reaction temperature could influence the formation of highly crystalline rutile phase of titania th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, these peaks low and weak intensity, which indicates that Cu2O did not fully grow on the TiO2 nanorods layer. The crystallite size of Cu2O phase was calculated by Scherrer equation [20]. It can be observed that the crystallite sizes of Cu2O increased when the deposition time increased as proven by the FWHM values as shown in Table 1.…”
Section: Structural Propertiesmentioning
confidence: 92%
“…However, these peaks low and weak intensity, which indicates that Cu2O did not fully grow on the TiO2 nanorods layer. The crystallite size of Cu2O phase was calculated by Scherrer equation [20]. It can be observed that the crystallite sizes of Cu2O increased when the deposition time increased as proven by the FWHM values as shown in Table 1.…”
Section: Structural Propertiesmentioning
confidence: 92%